Effects of mild hypothermia on serum HMGB1 of brain-dead donors and its impact on kidney transplantation recipients. Issue 22 (29th May 2020) - Shan, Hui; Zhang, Xin; Lin, Zhe-Min; Wang, Xue-Zhu; Mi, Zi-Xin; Wang, Ya-Ping; Tang, Zi-Ren; Zhang, Xiao-Dong
Abstract : Abstract: Investigate the effect of mild hypothermia on serum inflammatory factor HMGB1 of brain-dead donors, and its significance for renal transplantation recipients. In our hospital between January 2018 and January 2019 up to the standard of brain death donor (aged 18 to 65 years old) prospective cohort study, brain death donor were randomly divided into mild hypothermia group and the non-mild hypothermia group. Serum were collected from donor at different periods, and enzyme-linked immunoassay (ELISA) was used to determine the serum HMGB1 concentration to compare the difference between the 2 donor groups. The early recovery of renal function after renal transplantation was followed up, and the incidence of delayed graft function (DGF) and early recovery of renal function were compared between the 2 groups. The correlation between donor HMGB1 and recipient DGF was analyzed. Between 17 donors in the mild hypothermia group and 17 in the non-mild hypothermia group, there were no statistically significant differences in the age, perioperative urine volume and ICU stay between the 2 groups. After mild hypothermia treatment, serum HMGB1 levels of brain death donors were significantly decreased. While in non-mild hypothermia brain death donor group without treatment, serum HMGB1 was significantly increased. There were no statistically significant differences in age and preoperative creatinine between the 2 recipient groups, including 33 patients in the mild hypothermia group and 34 patients in the non-mild hypothermia group. DGF incidence was lower in mild hypothermia group comparing with non-mild hypothermia group with statistical significance. The levels of HMGB1 from donor before procurement is correlated with the occurrence of DGF of the recipient. Mild hypothermia therapy can reduce the levels of serum HMGB1, improve the function of donor organs. The levels of HMGB1 before donor procurement can be used to predict the occurrence of DGF in kidney transplant recipients. Our study shows that HMGB1 can be potentially used as therapeutic target of early intervention for brain death donors. Furthermore, mild hypothermia therapy can be applied in the maintenance of brain death donors for kidney transplant recipient to improve the successful rate of transplantation. Abstract : Supplemental Digital Content is available in the text